Aspectos fenotípicos celulares de leucócitos circulares em portadores de hepatite C crônica com ou sem insuficiência renal crônica - Katia Valeria Bastos Dias Barbosa (2008)
BACKGROUND AND AIMS: Chronic hepatitis C (CHC) and end-stage renal disease (ESRD) are common and potentially serious medical problems throughout the world. The immune system plays a key role in the natural history of hepatitis C virus (HCV) infection. However, the knowledge of immunological aspects of HCV infection in ESRD patients is still limited. Hence, we sought to investigate the profile of the immune response focusing on major phenotypic features of peripheral blood lymphocytes. Patients and Methods: Four groups were investigated: G1 - 15 blood donors (BD); G2- 19 patients with ESRD without HCV infection(ESRD); G3- 20 patients with and normal renal function (CHC); G4- 16 patients with CHC and ESRD in hemodialysis (CHC+ESRD). CHC was confirmed by HCV-RNA-PCR, high ALT levels and/or liver-biopsy. HIV, HBV, alcoholism, autoimmune liver-diseases, use of immunosuppressive drugs and transplanted patients were exclusion criteria. EDTAperipheral blood white cells were labeled with fluorochrome-conjugated specific monoclonal antibodies following immunofluorescence analysis by flow cytometry. RESULTS: Althoughno changes in the mean frequency of circulating T-cells, higher proportion of activated CD4+HLA-DR+ as well as CD8+HLA-DR+ T-cells was observed in CHC and CHC+ESRD as compared with BD. In addition, higher frequency of NKT-cell appeared as the hallmark of HCV infection, despite the presence of renal disease. On the other hand, the monocytic/macrophagic and B-cell compartment were the most affected by renal disease. Lower percentage of CD19+B-Lymphocytes parallel with significant decrease in the CD19+CD5+B1- subset and activated CD19+CD23+B-cells besides higher frequency of monocytes, both proinflammatory and macrophage-like, was observed in ESRD and HCH+ESRD as compared to BD. CONCLUSIONS: These findings suggest that despite the activation of T-cell subsets is the most affected by the HCV infection, the presence of ESRD is associated with significantimpairment of the B-cell compartment and activation of innate immunity, via monocyte activation. It might be implicated in the natural history of CHC in ESRD patients.